2014
DOI: 10.1371/journal.pone.0113782
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Silicon on Photosynthesis and Expression of Its Relevant Genes in Rice (Oryza sativa L.) under High-Zinc Stress

Abstract: The main objectives of this study were to elucidate the roles of silicon (Si) in alleviating the effects of 2 mM zinc (high Zn) stress on photosynthesis and its related gene expression levels in leaves of rice (Oryza sativa L.) grown hydroponically with high-Zn stress. The results showed that photosynthetic parameters, including net photosynthetic rate, transpiration rate, stomatal conductance, intercellular CO2 concentration, chlorophyll concentration and the chlorophyll fluorescence, were decreased in rice e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
116
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(130 citation statements)
references
References 68 publications
12
116
1
1
Order By: Relevance
“…In addition, the protective action of Si was observed in Oryza sativa under high levels of zinc (Zn) (Song et al 2014), Hordeum vulgare under high concentrations of chromium (Cr) and Cucumis sativus exposed to manganese (Mn) toxicity (Shi et al 2005).The tolerance to metal toxicity can be induced by the compartmentalization, chelation and/or immobilization of metal ions into the vacuole, cytoplasm, apoplast or/and cell wall. In addition, Britez et al (2002) described that Si decreased Al toxicity due to the formation of Al-Si complexes in the apoplast, which are non-toxic forms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the protective action of Si was observed in Oryza sativa under high levels of zinc (Zn) (Song et al 2014), Hordeum vulgare under high concentrations of chromium (Cr) and Cucumis sativus exposed to manganese (Mn) toxicity (Shi et al 2005).The tolerance to metal toxicity can be induced by the compartmentalization, chelation and/or immobilization of metal ions into the vacuole, cytoplasm, apoplast or/and cell wall. In addition, Britez et al (2002) described that Si decreased Al toxicity due to the formation of Al-Si complexes in the apoplast, which are non-toxic forms.…”
mentioning
confidence: 99%
“…In addition, the protective action of Si was observed in Oryza sativa under high levels of zinc (Zn) (Song et al 2014), Hordeum vulgare under high concentrations of chromium (Cr) and Cucumis sativus exposed to manganese (Mn) toxicity (Shi et al 2005).…”
mentioning
confidence: 99%
“…2D), especially with the incorporation of Si in the nutrient solution. The addition of Si could protect the photosynthetic pigments in leaves, alleviating the damage to chloroplast ultrastructure, and increasing the expression of genes associated with photosynthesis (Song et al, 2014). The silicon, after being absorbed as monossilicic acid, is accumulated in the abaxial region of the leaves, making them upright and with greater light absorption and increasing the enzymatic activities responsible for the reduction and assimilation of nitrogen (Feng et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Among these, 18 matching to 11 proteins were related to CO 2 assimilation/photosynthesis processes, representing the largest functional category group of proteins that were differentially expressed due to Cd and/or Si treatments. More recently, based on the results regarding Si-improved photosynthesis parameters and chloroplast ultrastructure under high-Zn (2 mM) stress, Song et al ( 2014 ) have analysed the results of high-throughput sequencing and selected the main photosynthesis-related genes that were differentially expressed (see Fig. 5.12 ).…”
Section: Molecular Aspects Of Si-mediated Metal Resistancementioning
confidence: 99%
“…According to the results of high-throughput sequencing (Fig. 5.12 ), Song et al ( 2014 ) investigated the expression levels of the photosynthesis-related genes by using fl uorescent real-time qPCR and showed that the expression levels of photosynthesis-related genes including Os08g02630 ( PsbY ), Os05g48630 ( PsaH ), Os07g37030 ( PetC ), Os03g57120 ( PetH ), Os09g26810 and Os04g38410 decreased in Si-deprived rice plants under high-Zn (0.2 mM Zn) stress, while the addition of 1.5 mM Si increased the expression levels of these genes in plants under high-Zn stress at 72 h, and the expression levels were higher in Si-treated plants than in Si-deprived plants. Similar work was also done by Li et al ( 2011 ).…”
Section: Molecular Aspects Of Si-mediated Metal Resistancementioning
confidence: 99%